Manajemen pengelolan Zakat Produktif dan Integrasinya dalam Penguatan Ketahanan Pangan Masyarakat Kota Kediri - Dwi Budiarto; Anta Gusnanda; Zainal Mustofa (Jurnal Manajemen Dakwah, 2026)
This study aims to analyze productive zakat management and its integration in strengthening community food security in Kediri City. Using a qualitative approach through in-depth interviews, observation, and documentation at BAZNAS Kediri City. The findings reveal that productive zakat management operates effectively through performance-based planning, implemented via the Kediri Peduli program as a social safety net and Kediri Makmur as an economic empowerment instrument, both contributing to increased income and household food security among mustahik. However, limited institutional capacity, amil human resource readiness, and low public zakat literacy remain key obstacles. This study concludes that strengthening integrated zakat governance is essential to optimize zakat's role as an economic empowerment instrument and sustainable community food security.